2009
DOI: 10.4149/gpb_2009_04_420
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency magnetic field exposure affects DnaK and GroEL expression in E. coli cells with impaired heat shock response

Abstract: Abstract. In our earlier experiments, we found that extremely low frequency magnetic fields (ELF-MF) affect heat shock protein (HSP) expression in wild type Escherichia coli cells. In the present work we investigate the ability of ELF-MF exposure to trigger an increase of DnaK and GroEL protein levels also in E. coli cells not exhibiting the classic heat shock response (HSR) when subjected to a 42°C heat stress. We find that these cells, although lacking a HSR to heat shock treatment, show an enhancement of Dn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In this respect, genes induced by stressful agents represent suitable candidates. Indeed, it has been shown that exposure to ELF can induce an increase in the intracellular levels of the heat shock protein (HSP) 70 in a number of systems (Alfieri et al, 2004; Alfieri et al, 2006; Bernardini et al, 2007; Bernard et al, 2008; Del Re et al, 2009; Garip and Akan, 2010). HSP70 is a molecular chaperone whose induction is part of stress response (Ilangovan et al, 2006; Liu et al, 2006; Miyabara et al, 2006; Rafiee et al, 2006) and is mediated in higher eukaryotes by the activation of heat shock transcription factor 1 (HSF1), a master regulator that binds to responsive regions in stress‐inducible genes (Morimoto, 1998).…”
mentioning
confidence: 99%
“…In this respect, genes induced by stressful agents represent suitable candidates. Indeed, it has been shown that exposure to ELF can induce an increase in the intracellular levels of the heat shock protein (HSP) 70 in a number of systems (Alfieri et al, 2004; Alfieri et al, 2006; Bernardini et al, 2007; Bernard et al, 2008; Del Re et al, 2009; Garip and Akan, 2010). HSP70 is a molecular chaperone whose induction is part of stress response (Ilangovan et al, 2006; Liu et al, 2006; Miyabara et al, 2006; Rafiee et al, 2006) and is mediated in higher eukaryotes by the activation of heat shock transcription factor 1 (HSF1), a master regulator that binds to responsive regions in stress‐inducible genes (Morimoto, 1998).…”
mentioning
confidence: 99%
“…The high expression of groEL and the co-chaperone groES can enhance the cellular resistance to environmental stress to preserve regular metabolic activities and cell structural integrities. 52 Besides, co-expression of fkpA , a gene encoding periplasmic chaperone, was found to be effective in regaining the cell physiology and alleviating the extra-cytoplasmic stress response. 53 Although the expressions of chaperone-related transcripts displayed no differences in the stressed cells with those in the control, they were all dramatically up-regulated under the mediation of C 6 -HSL (Table S2†).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few investigations have examined how exposure to electromagnetic fields of extremely low frequency affects biofilms in bacteria. Many studies suggest that exposure to ELF results in stress responses that alter cell phenotype and transcription, as well as surface adherence in biofilm-forming cells [23]. Karaguler et al, [29] examined the impact of EMF by exposing Gram -ve P. aeruginosa and Gram +ve S. epidermidis for 24 h to 50 Hz frequency of the field and were comparable with the corresponding controls who hadn't been exposed.…”
Section: Effect Of Elf-emf On Biofilm Formationmentioning
confidence: 99%